Communication and Kinship. On “Koinōnia” and “Syngeneia” in Plato’s Dialogues - Delle Donne, Carlo (2022)
The purpose of this paper is to shed light on the multiple functions of the notion of koinōnia in Plato’s dialogues. Koinōnia and its absence characterize reality as a whole: both the intelligible and the sensible entities either “communicate” or do not “communicate” (koinōnein); therefore, reconstructing the net of koinōnia-relationships amounts to putting dialectics into practice. So far so good. But an analysis which aims at clarifying the role played by koinōnia cannot but take also syngeneia into account. The reason for this fact lies in the essential link which binds koinōnia and syngeneia, with the latter being the condition of possibility of the former.